Modulation of growth-related protein expression of native chicken in low altitude in West Jawa, Indonesia (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objective of this study was to evaluate the response-ability of local chickens to their rearing habitat, especially at low altitudes, to comprehensively understand the cellular response related to protein growth. Materials and Methods: Studies of cellular responses related to modulation and growth-related protein salinization for three local Indonesian chicken breeds to low altitudes with high temperatures have been conducted in two locations with altitudes